Peran Mahasiswa KKN di Desa Talawi Hilie dalam Meningkatkan Karakter Anak-anak dengan Sosialisasi bullying - Lisa Putriani; Friskha Hapsari; Mualimin Ramadhan; Wanda Agustin; Muhammad Revo Alvarenza; Annisa Febriadmi Candra (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2025)
Real work lectures are useful in helping students to realize the younger generation, especially children. One of them is bullying prevention socialization activities. Researchers explain education about bullying. Forms of bullying, the impact and prevention of bullying. This activity is desired to be able to explain the benefits for schools, parents and students so as to reduce bullying that occurs. This research method uses a qualitative approach with a case study design chosen to explore the dynamics of implementing a bullying socialization program with the aim of improving and preventing bullying in Talawi hilie village. The results of the analysis are presented in narrative form so as to provide a clear picture of the field conditions and the perspective of school residents on the program that is running. The results of the socialization activities show that students have a good understanding of bullying and after participating in this bullying socialization activity, students are able to explain the definition of bullying as “repeated behavior by a person or group with the aim of hurting both at school, and other social environments”. They also understand the prevention of bullying such as, education and socialization, increasing empathy and attention and reporting if they get bullying. It can be concluded that this activity motivates the community, especially elementary school students in Talawi Hilie Village, to prevent bullying. Bullying socialization activities are carried out well and there is an increase in bullying prevention to improve the character of good children.